Sistem Administrasi Pendidikan dalam Meningkatkan Mutu Pendidikan - Nurul Huda (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2022)
This article describes the results of research in one of the educational institutions on the island of Bawean, namely Madrasah Aliyah Hasan Jufri. The importance of the education administration system to be implemented is one of the benchmarks for the quality of education, especially in the teaching and learning process, but in its application it is still not optimal. This study aims to answer the problem of the education administration system in improving the quality of education by using descriptive qualitative research methods. The results of this study indicate that it is necessary to organize an education administration system to improve the quality of education, including (1) management of the teaching and learning process, (2) evaluation planning, (3) curriculum management, (4) manpower management, (5) facility management, (6) financial management, (7) student services, (8) cooperation or relations with the community, and (9) a conducive academic climate in madrasa.